The Social Consequences of the Novel Coronavirus Disease (COVID-19) Outbreak in Iran: Is Social Capital at Risk? A Qualitative Study - Motamed-Jahromi, Mohadeseh; Kaveh, Mohammad Hossein (Interdisciplinary Perspectives on Infectious Diseases, 2021)
As well as causing a global health crisis, the COVID-19 pandemic has also generated multilevel social changes by damaging psychosocial and economic resources across Iranian society. Therefore, this qualitative study was conducted to examine and explain these social consequences and their impact on the social capital of Iran during the COVID-19 outbreak. Using a content analysis approach, nine experts participated in semistructured, in-depth interviews. Interviews were recorded and transcribed verbatim and analyzed using Lundman and Graneheim’s method. The social impacts of COVID-19 can be summarized into six categories and 32 subcategories. Three positive-negative categories emerged from the data analysis: “formation of new patterns of social communications; formation of new patterns of behavior; creation of economic changes.” Three entirely negative categories included “creating a climate of distrust; disruption of cultural, social, and religious values; psychosocial disorders.” Overall, most findings (27 out of 32 subcategories) indicated the destructive effects of the COVID-19 pandemic on social capital. Therefore, this raises concerns about social capital endangerment in Iran. However, positive social impacts can guide policies that strengthen social action and improve social capital.